DIGITALIZATION AND ECONOMIC GROWTH: A BIBLIOMETRIC ANALYSIS - Shihab, Ruba Nimer Abu; Istaiteyeh, Rasha; Kreishan, Fuad M.; khaliq, Shatha Abdul (Journal of Posthumanism, 2025)
The Digital Economy (DE) has significantly impacted the global economy. This paper presents a bibliometric analysis to explore the impact of digitalization on economic growth, covering literature from 2008 to 2024 sourced from the Scopus database. It aims to map the intellectual contours and evolution of research within economics, econometrics, finance, business, management, accounting, and environmental studies. The study identifies key themes, influential works, and authors by employing advanced data mining, visualization, and analytical techniques while highlighting theoretical and empirical underpinnings that connect digitalization with economic expansion. The analysis discerns a scholarly trajectory from the foundational role of digital technologies in economic development to a nuanced understanding of digitalization's interplay with sustainability and specific innovations like blockchain and Industry 4.0. The recent focus emphasizes integrating digital growth with sustainable development goals, indicating a shift towards examining the environmental impacts of digital advancements. This comprehensive overview charts the dynamic shifts in scholarly focus and underscores the significance of interdisciplinary approaches in navigating the complexities of digitalization's effects on economic growth, offering a roadmap for future research directions.